2015
DOI: 10.1007/s00405-015-3770-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of deviated nasal septum on the structure of nasal cavity

Abstract: The present study was aimed to investigate the effects of DNS on the structure of nasal cavity. The paranasal sinus coronal view CT of 108 patients with DNS and 129 hospitalized patients without DNS was retrospectively analyzed. The transverse diameter of nasal cavity (a), transverse diameter of nasal cavity and paranasal sinus (b), angle between maxillary and palatal bone, interalveolar distance, and maxillary rotation distance were measured. The ratio of a/b in experimental group was 0.367 ± 0.006 which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…Nasal septum deviation (NSD) that describes a non-straight, deformed nasal septum is a common abnormality and can be observed in 80% of the population ( Serifoglu et al, 2017 ). NSD might be inconspicuous but frequently is associated with various degrees of nasal airway obstruction resulting in Sleep Disordered Breathing (SDB) ( Wang et al, 2016 ; Alsufyani et al, 2017 ; Mandour et al, 2019 ). Congenitally acquired deviation frequently develops during time of rapid midfacial growth and is associated with reduced midfacial growth and a strong predisposition for SDB ( D’Ascanio et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nasal septum deviation (NSD) that describes a non-straight, deformed nasal septum is a common abnormality and can be observed in 80% of the population ( Serifoglu et al, 2017 ). NSD might be inconspicuous but frequently is associated with various degrees of nasal airway obstruction resulting in Sleep Disordered Breathing (SDB) ( Wang et al, 2016 ; Alsufyani et al, 2017 ; Mandour et al, 2019 ). Congenitally acquired deviation frequently develops during time of rapid midfacial growth and is associated with reduced midfacial growth and a strong predisposition for SDB ( D’Ascanio et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nasal septum is located in the medial portion of the nasal cavity and it is on the major part of the nose structure. It is divided into a posterior part by the vomer and perpendicular plate of the ethmoid bone and an anterior part by the quadrangular cartilage [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…When we consider healthy nasal respiration the anatomical and morphological characteristics of the bony and cartilaginous parts of the nasal septum play an important role. Nasal septal deviation is also linked to sleep apnea, repetitive sneezing, nosebleeds, sinusitis and difficulty breathing [ 1 ]. Some investigators linked the sense of smell sense with septal deviation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, NSD occurs secondary to trauma during intrauterine life, birth, or any time during life 7 . It is reported that NSD may be related to sleep apnea, nosebleeds, repetitive sneezing, difficulty in breathing, and chronic sinusitis 8 . The deviation of the nasal septum causes change in the air flow in the nasal cavity, nasal cycle and mucociliary clearance.…”
Section: Introductionmentioning
confidence: 99%